Metaverse in tourism and hospitality industry: science mapping of the current and future trends - Nazim Hanis Zainal Abidin; Muhammad Ashraf Fauzi; Walton Wider; Wan Muhammad Noor Sarbani Mat Daud; Rusnifaezah Musa (Journal of Tourism Futures)
Purpose – This study performs a science mapping approach based on bibliometric analysis of the metaverse and its associated technology in tourism and hospitality. As an immersive technology, metaverse has penetrated various segments of human life and business activities. This digital transformation phenomenon has also penetrated tourism and hospitality in mixed reality, comprising virtual, augmented and extended reality. Design/methodology/approach – The knowledge structure of the past and future trends in the sector’s metaverse application is analyzed to present the topological and temporal structure by a science mapping approach. Findings – Findings show that current and emerging trends are related to tourism mobilities, cultural and heritage tourism, digital landscape transformation and motivation to adopt virtual reality. At the same time, future trends suggest three themes related to the transformation of the tourism industry through the metaverse: immersive heritage exploration, technology adoption in metaverse tourism. Research limitations/implications – Metaverse technology will continue impacting tourism services and product offerings. Stakeholders and players in the tourism sector need to adapt to the development of metaverse technology to stay competitive and relevant in today’s digital environment. Originality/value – Through a science mapping approach, this study offers a crucial temporal and structural understanding of the metaverse in tourism phenomenon.